Magnetic nanoparticles as a versatile solid-support for fusion protein purification and antimicrobial assays - Fernandes, Cláudia Sofia Mendes (2014)
Magnetic nano-and microparticles are unique platforms for the development of bioseparation and antimicrobial devices. This work explored the application of magnetic particles for the purification of fusion proteins through the use of magnetic adsorbents coupled to novel affinity ligands towards peptidic and proteic tags. Furthermore, and in view of the novelty of these ligands, molecular modeling and simulation techniques were employed to explain the key structuralfeatures involved inthe binding of two affinity pairs: GFP/LA-A4C7 and RK-GFP/LR-A7C1.The results showed that the interaction between GFP and LA-A4C7 is mainly hydrophobicwhile the interaction between RK-GFP and LR-A7C1 is mostly driven byhydrogen bonds. Moreover, the same modeling techniques have been used to idealize a theoretical second generation library with view of maximizing the estimated free energy of binding and the correspondent affinity constant. When immobilizing the biomimetic ligands LA-A4C7 and LR-A7C1 onto magnetic nanoparticles, it was possibleto bind the protein of interest and recover pure elution fractions. The best elution condition for GFP elution was 0.1mM glycine-NaOH pH9 50% (v/v) ethylene glycoland the best elution condition for RK-GFP elution was PBS pH 7.4, 500mM arginine, which are in accordance with the theoretical results described previously. Final binding constants for the studied systems (Ka=0.83×105M-1and Qmax=4mg/g for GFP/LA-A4C7, Ka=3.21×105M-1and Qmax=2mg/g for RK-GFP/LR-A7C1) show promising results for an affinity-based protein purification system.Magnetic particleswere also functionalized with (RW)3, an peptidewith antimicrobial properties, by different routes. We were able to develop a novel antimicrobial nanodevice based on the EDC-coupling of (RW)3that has shown antimicrobial activity against Escherichiacoliand Bacillussubtilis.